Intact P4 Tetrahedra as Terminal and Bridging Ligands in Neutral Complexes of Manganese1. Issue 41 (3rd September 2013) - Heinl, Sebastian; Peresypkina, Eugenia V.; Timoshkin, Alexey Y.; Mastrorilli, Piero; Gallo, Vito; Scheer, Manfred
<x xml:space="preserve">Abstract</x> Static dynamic: Neutral, end‐on bound white‐phosphorus complexes with unprecedented stability in the solid state and solution were synthesized (see structure: gray C, blue Mn, red O, violet P). While the C5(4‐nBuC6H4)5 ligands are stationary at low temperature on the NMR timescale, the P4 ligands rotate rapidly. Despite the unfavorable γP/γH ratio, a heteronuclear Overhauser effect between the protons in ortho position and the basal P atoms was detected.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>